Macroprudential policy in a monetary union with cross-border banking - Matthieu Darracq Pariès; Christoffer Kok Sørensen; Elena Rancoita (European Central Bank (ECB), 2019)
We analyse the interaction between monetary and macroprudential policies in the euro area by means of a two-country DSGE model with financial frictions and cross-border spillover effects. We calibrate the model for the four largest euro area countries (i.e. Germany, France, Italy, and Spain), with particular attention to the calibration of cross-country financial and trade linkages and country specific banking sector characteristics. We find that countercyclical macroprudential interventions are supportive of mon-etary policy conduct through the cycle. This complementarity is significantly reinforced when there are asymmetric financial cycles across the monetary union, which provides a case for targeted country-specific macroprudential policies to help alleviate the burden on monetary policy. At the same time, our findings point to the importance of taking into account cross-border spillover effects of macroprudential measures within the Monetary Union.
Keywords: E32; E44; E52; F36; F41; 330; monetary policy; macroprudential policy; DSGE; banking